Hip Pain 10 years after Total Hip Replacement - Lik Han, Ong; Sabaruddin, Abdullah; Ankimtay, Rutel; Reuben, P. Rao; A. A., Redzuan; 3E-Vick, Duin; X. Y., Ang; Faris, Kamaruddin
Femoral stem fracture following total hip arthroplasty (THA) is an infrequent but devastating complication with incidence of 0.1 to 3.4%.1 Loss of proximal support with a well-fixed distal stem causes cantilever bending that later promote localized corrosion, fretting and fatigue crack initiation leading to stem failure.